The Role of Evidence in Proving the Element of Intent in Murder Cases - Bambang Sasmita Adi Putra; Tumian Lian Daya Purba; Hamzah Mardiansyah; Nining Suningrat; Yanto Irianto (Universitas Muhammadiyah Palu, 2025)
This study examines the role of evidence in proving intent in murder cases within the criminal justice system. Intent is an element in distinguishing between different types of homicide, such as premeditated murder and manslaughter. The complexity of proving intent is influenced by the types of evidence available, including direct, circumstantial, forensic, and testimonial evidence. Direct evidence, such as confessions or eyewitness testimony, is the most definitive but is often unavailable, making circumstantial evidence essential in many cases. Forensic evidence, particularly autopsy results, provides significant insights into whether the actions were deliberate or accidental. Motive also plays an important role in strengthening the case for intent, offering contextual understanding of the perpetrator's reasons for committing the crime. Witness testimony, although important, requires careful evaluation to ensure its reliability. Psychological factors, such as emotional distress or provocation, can further complicate proving intent, as they may reduce the level of premeditation and influence the legal classification of the crime. This paper argues that proving intent in murder cases requires a comprehensive approach that integrates multiple forms of evidence to ensure accurate legal outcomes and fair justice.